Smallholder Farmers and Climate Smart Agriculture: Technology and Labor-productivity Constraints amongst Women Smallholders in Malawi. (1st January 2016) - Murray, Una; Gebremedhin, Zewdy; Brychkova, Galina; Spillane, Charles
Abstract: Climate change and variability present a major challenge to agricultural production and rural livelihoods, including livelihoods of women smallholder farmers. There are significant efforts underway to develop, deploy, and scale up Climate-Smart Agricultural (CSA) practices and technologies to facilitate climate change adaptation for farmers. However, there is a need for gender analysis of CSA practices across different farming and cultural systems to facilitate adoption by, and livelihood improvements for, women smallholder farmers. Climate change poses challenges for maintaining and improving agricultural and labor productivity of women smallholder farmers. The labor productivity of many women smallholders is constrained by lack of access to labor-saving technologies and the most basic of farm tools. Poorer smallholders face a poverty trap, due to low agricultural and labor productivity, from which they cannot easily escape without access to key resources such as rural energy and labor-saving technologies. In Malawi, the agricultural system is predominantly rainfed and largely composed of smallholders who remain vulnerable to climate change and variability shocks. Despite the aspirations of women smallholders to engage in CSA, our research highlights that many women smallholders have either limited or no access to basic agricultural tools, transport, and rural energy. This raises the question of whether the future livelihood scenarios for such farmers will consist of barely surviving or "hanging in"; or whether such farmers can "step up" to adapt better to future climate constraints; or whether more of these farmers will "step out" of agriculture. We argue that for women smallholder farmers to become more climate change resilient, more serious attention to gender analysis is needed to address their constraints in accessing basic agricultural technologies, combined with participatory approaches to develop and adapt CSA tools and technologies to their needs in future climates and agro-ecologies.